2022
DOI: 10.3389/fnins.2022.804261
|View full text |Cite
|
Sign up to set email alerts
|

Methylated Cytochrome P450 and the Solute Carrier Family of Genes Correlate With Perturbations in Bile Acid Metabolism in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is second most prevalent neurodegenerative disorder following Alzheimer’s disease. Parkinson’s disease is hypothesized to be caused by a multifaceted interplay between genetic and environmental factors. Herein, and for the first time, we describe the integration of metabolomics and epigenetics (genome-wide DNA methylation; epimetabolomics) to profile the frontal lobe from people who died from PD and compared them with age-, and sex-matched controls. We identified 48 metabolites to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Our results have shown no significant correlation between PWY-5913 and significantly different microbes, which indicated that this different pathway uncovered a whole-level difference. Meanwhile, CYP39A1 encoded a member of the cytochrome P450 superfamily of enzymes and played an important role in tumor progression ( Khenjanta et al, 2014 ; Ji et al, 2022 ) and neurodegenerative disorder ( Vishweswaraiah et al, 2022 ). CYP39A1 might affect a variety of microbes and finally show the difference in the PWY-5913 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have shown no significant correlation between PWY-5913 and significantly different microbes, which indicated that this different pathway uncovered a whole-level difference. Meanwhile, CYP39A1 encoded a member of the cytochrome P450 superfamily of enzymes and played an important role in tumor progression ( Khenjanta et al, 2014 ; Ji et al, 2022 ) and neurodegenerative disorder ( Vishweswaraiah et al, 2022 ). CYP39A1 might affect a variety of microbes and finally show the difference in the PWY-5913 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the aforementioned studies used Gene Ontology analysis to examine the functions of genes with altered methylation. Some of the key processes affected were neuronal development and differentiation, synaptic transmission, neurotransmitter transport, dopaminergic synapse, metabolism, immunity, bile acid secretion, cell cycle and cell signaling (including the Wnt pathway), all of which have been implicated in PD pathogenesis [ 87 , 91 , 93 , 94 , 98 , 101 ].…”
Section: Dna Methylationmentioning
confidence: 99%
“…In early PD, accelerated hematopoietic cell mitosis was revealed, possibly reflecting immune pathway imbalances, which may be related to motor and cognitive progression [ 64 ]. The integration of metabolomics and epigenetics (genome-wide DNA methylation; epimetabolomics) was described after studies of the frontal lobe of people who died from PD: 48 metabolites and 4313 differentially methylated sites were identified in the primary motor cortex of people who died from PD, as compared with age- and sex-matched controls [ 65 ]. The metabolite taurine level correlated with CpG methylated sites, and bile acid biosynthesis was the major biochemical pathway to be perturbed in the frontal lobe of PD sufferers.…”
Section: Familial and Sporadic Forms Of Pd Epigenetic Aspectsmentioning
confidence: 99%